2020
DOI: 10.21831/cp.v39i2.29316
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the Forest School Framework Based on Indigenous Knowledge in Malaysia

Abstract: The rate of drop outs among indigenous or Orang Asli pupils in primary school is a worrying issue. They were found to be unable to apply the knowledge acquired through formal education systems in Malaysia due to the different 'setting' of the environment. This failure was due to the lack of understanding on how Orang Asli pupils learn, think, and act. The aim of this study was to construct a Forest School framework for the teaching and learning process in Orang Asli primary schools. The qualitative study desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Ideally, the pedagogy of the Indigenous school propositions consists of a learning involvement that matches their children's needs and cultural practices (Wahab et al, 2020). Mustapha et al (2018) suggested bridging the academic subject content with cultural knowledge when strategizing rural school propositions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, the pedagogy of the Indigenous school propositions consists of a learning involvement that matches their children's needs and cultural practices (Wahab et al, 2020). Mustapha et al (2018) suggested bridging the academic subject content with cultural knowledge when strategizing rural school propositions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Absenteeism has been the number one issue among Indigenous community school children. One of the factors behind this phenomenon is that they do not understand the syllabus teachers convey (Wahab et al, 2020). As they have their own capacity for absorbing new information, they face difficulties relating the information taught in the classroom to their living environment.…”
Section: Introductionmentioning
confidence: 99%
“…Leaving the task of educating Orang Asli children to the JAKOA to improve their condition was futile. They were found to be unable to apply the knowledge acquired through formal education system in Malaysia due to the different settings of the environment (Wahab et al, 2020). The problem is that despite support from the government and other agencies, Orang Asli students remain underachieving and remain disengaged from school (Misnaton, Hamidah & Marinah, 2016).…”
Section: Orang Aslimentioning
confidence: 99%
“…Individual factors are internal considerations within the individual. The knowledge-sharing ability of each individual is different (Wahab et al, 2020). One of the causes of the low ability arises from the individual.…”
Section: Introductionmentioning
confidence: 99%